Media and elections democratic transition in Malaysia - Gomez, James 1965-; Mustafa K. Anuar; Yuen, Beng Lee (Strategic Information and Research Development Centre, 2018)
Media and Elections: Democratic Transition in Malaysia examines the central role of the media in Malaysian electoral contests. The book unpacks how a potent mix of regulation and crony media ownership in Malaysia has created a mainstream media that is biased towards the ruling regime, especially during elections. Drawing from research into how the different media tried to impact voter behaviour during the 13th General Election, the authors in this volume forecast that the online landscape is where the communications contest will play out in the 14th General Election. In the run up to the next general election, political opinion continues to be polarised over social media in Malaysia. This has prompted the government to legislate the online space which has in turn implications for freedom of expression. This book is highly recommended to academics, analysts, civil society activists, commentators, election candidates, journalists, media owners, voters and all others interested in freedom of expression and online electoral communications is Malaysia.